2022
DOI: 10.1101/2022.07.07.499172
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-associated changes in knee osteoarthritis, pain-related behaviors, and dorsal root ganglia immunophenotyping of male and female mice

Abstract: Objective: Osteoarthritis (OA) is a leading cause of chronic pain, yet OA pain management remains poor. Age is the strongest predictor of OA development, and mechanisms driving OA pain are unclear. While injury-induced OA models are useful, only a subset of OA is linked to traumatic injury. Here, we aimed to characterize age-associated joint damage, mechanical sensitization, and dorsal root ganglia (DRG) immune phenotypes in mice of both sexes. Methods: Male or female mice aged 6- or 20-months old were evaluat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 85 publications
3
10
0
Order By: Relevance
“…Similar to the findings of sex differences in spontaneous age‐related OA and pain‐like behavior reported by Geraghty et al (4), a study of posttraumatic knee OA in 10‐week‐old C57BL/6 male and female mice noted more severe histologic OA in male mice, yet female mice exhibited similar levels of pain behavior (13). In a gene knockout study of cartilage acidic protein 1 using a DMM model, female but not male mice exhibited less severe OA and gait abnormalities used as a measure of pain‐like behavior (14).…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Similar to the findings of sex differences in spontaneous age‐related OA and pain‐like behavior reported by Geraghty et al (4), a study of posttraumatic knee OA in 10‐week‐old C57BL/6 male and female mice noted more severe histologic OA in male mice, yet female mice exhibited similar levels of pain behavior (13). In a gene knockout study of cartilage acidic protein 1 using a DMM model, female but not male mice exhibited less severe OA and gait abnormalities used as a measure of pain‐like behavior (14).…”
supporting
confidence: 81%
“…In humans, the severity of radiographic OA correlates more strongly with pain in men than in women (9). Geraghty et al (4) found that despite less severe histologic OA in female mice, they exhibited similar, if not more severe, pain‐like behavior than the male mice. In both sexes, pain was associated with increased percentages of macrophages and dendritic cells in the DRGs, while the DRG immunophenotypes of male and female mice differed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These 2 models are induced by either surgical cutting of the MMTL or both the MMTL and medial meniscus respectively, which likely explains the predominantly medial side changes. In comparison, mild age associated changes in the synovium were previously observed in both medial and lateral joint compartments (35,36).…”
Section: Discussionmentioning
confidence: 82%
“…Our recommendations, which were informed by currently published methods, are summarized in ( Table 4 ). Of note, we have utilized this system in a previous studies (35,36) with reproducible results to gain insight into aging-related changes to the synovium in mice.…”
Section: Discussionmentioning
confidence: 99%